DIVERSITY OF ARTHROPOD PREDATOR IN SWAMP RICE FIELDS IN SOUTH SUMATERA - Meidalima, Dewi; Kawaty, Ruarita Ramadhalina; B. Gunawan, Erlan (Universitas Lampung, 2018)
The abundance and diversity of arthropod in agro ecosystem depend on the level of synthetic pesticide contamination. This study aimed to explore, identify and analyze the diversity and abundance of predatory arthropods in swamp rice fields treated with pesticide application (in Pemulutan) and without pesticide application (in Musi 2). The swamp rice fields in Pemulutan are bordered by village, river and forest. The methods were survey and direct observation on 3 ha and 2 ha of swamp rice fields in Pemulutan and Musi 2, Palembang. Sampling of predatory arthropods were conducted at 20, 50, 80 and 110 days after rice planting using pitfall trap. Identification of predatory arthropods was conducted at Laboratory of Entomology showing that the arthropod collected consisted of 17 species of insects and 9 species of Arachnida. In Pemulutan Ogan Ilir were found 19 species (10 species of insect and 9 species of Arachnida) at the village area. In the area that was bordered by river were found 8 species (7 insect and 1 Arachnida). In the area bordered by forest were found 22 species (10 species of insects and 12 species of Arachnida). The diversity level, number of species, and arthropod specimen in the field without pesticide application at Musi 2 were higher than those in the fields with pesticide application in Pemulutan.